Company Laws Ii India: Comparative Analysis of Companies Act 1956 and Companies Act 2013 - Kapoor, Anil; Diksha; Verma, D.P. (Journal of Law and Humanity Studies, 2024)
The concept of a company act was inspired by the English Companies Act of 1844. The Joint Stock Companies Act, India's first company legislation, was enacted in 1850. This Act was succeeded by the Joint Stock Companies Act of 1857, which introduced the notion of limited liability in India for the first time. The concept of a company act was inspired by the English Companies Act of 1844. The Joint Stock Companies Act, India's first company legislation, was enacted in 1850. This Act was succeeded by the Joint Stock Companies Act of 1857, which established limited liability for the first time in India. The corporate sector in India is diversified, and the law, like a living creature, governs the corporate sector of any economy. On the one hand, it is made up of multinational corporations, but it also comprises a large number of small and medium-sized businesses that fuel growth and inject dynamism into the sector. This intriguing patchwork of Corporate India has contributed significantly to India's economic growth. In this study, the researcher attempted to focus on several aspects of company law. For this objective, the researcher collected data from primary and secondary sources.